Moral Pluralism in Debus Performing Arts: Phenomenological Analysis of Cultural Communication in Banten - Idi Dimyati; Ahmad Sihabudin; Melati Mediana Tobing (Jurnal Komunikasi Ikatan Sarjana Komunikasi Indonesia, 2025)
The Debus performing art of Banten, which has existed since the Sultanate era, now faces complex challenges. On one hand, there are issues of preserving traditional values, while on the other there is the pressure of modernization. Moreover, Debus, which is often associated with magical elements, frequently triggers negative stigmas, whereas the moral pluralism inherent within has not been thoroughly explored. This problem is the focus of the current study. This research applies a qualitative phenomenological approach through participatory observation of Debus performances, in-depth interviews with 10 informants (Debus artists), focus group discussions, and literature studies. Data analysis employs Interpretative Phenomenological Analysis (IPA). The findings show that Debus artists construct the meaning of moral pluralism through the integration of Islamic spiritual values, cultural resilience, and symbolic negotiation. These findings are consistent with Mead's theory of symbolic interactionism and Rawls's moral pluralism theory regarding the coexistence of values in multicultural societies. Negative stigma against Debus mostly stems from a gap in understanding (stock of knowledge) between the artists and the public. The study concludes that Debus represents a unique model of moral pluralism through dynamic and complex practices of cultural communication. Public education and progressive cultural policy are required to reduce stigma and support its preservation as Indonesian cultural heritage.